Effect Size Model Pembelajaran Project Based Learning Berbasis IoT terhadap Keterampilan Berpikir Abad 21 Siswa: Effect Size IoT Based Project Based Learning Model on Students 21st Century Thinking Skills - Baso Intang Sappaile; Andi Yustira Lestari; Nadriyah; Andri Kurniawan; Ellina Rienovita; Sukini; Tomi Apra Santosa (ASOSIASI IDEBAHASA KEPRI, 2024)
This research aims to determine the effect of IoT based Project Based Learning on Students' 21st Century Skills. This type of research is a meta-analysis research type. The data source in this research comes from an analysis of 13 journals published 2020-2024. Data source search process via Google Scholar, ScienceDirect, Researchgate, Taylor of Francis and ERIC. Data search keywords are Internet of Things, Project Based Learning, Influence of IoT based on Project Based Learning on students' critical thinking skills. Data collection techniques are direct observation and documentation. Data analysis calculates the effect size value of the entire research using the JSAP application. The results of this research conclude that there is an influence of the Internet of Things based on project based learning on students' critical thinking skills with an average effect size value of 1.18 in the high effect size category. These findings show that the application of the Internet of Things based on project based learning is effective in encouraging students' critical thinking skills